2023
DOI: 10.3389/fbioe.2023.1193376
|View full text |Cite
|
Sign up to set email alerts
|

Finite element study of the biomechanical effects on the rotator cuff under load

Abstract: Rotator cuff injuries account for 50% of shoulder disorders that can cause shoulder pain and reduced mobility. The occurrence of rotator cuff injury is related to the variation in shoulder load, but the mechanical changes in the rotator cuff caused by load remain unclear. Therefore, the mechanical results of the rotator cuff tissue during glenohumeral abduction and adduction were analyzed based on a finite element shoulder model under non-load (0 kg) and load (7.5 kg) conditions. The results showed that the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…[11] With the rapid development of digital medicine, the application of nite element analysis (FEA) in the eld of shoulder joints has become increasingly prevalent. [12] Through computer simulation modeling and analysis under different loading conditions, FEA helps overcome the limitations of traditional biomechanics. Currently, researchers have incorporated nite element analysis into the study of shoulder joints, focusing on areas such as the mechanisms of rotator cuff tears and the surgical treatment of such tears.…”
Section: Discussionmentioning
confidence: 99%
“…[11] With the rapid development of digital medicine, the application of nite element analysis (FEA) in the eld of shoulder joints has become increasingly prevalent. [12] Through computer simulation modeling and analysis under different loading conditions, FEA helps overcome the limitations of traditional biomechanics. Currently, researchers have incorporated nite element analysis into the study of shoulder joints, focusing on areas such as the mechanisms of rotator cuff tears and the surgical treatment of such tears.…”
Section: Discussionmentioning
confidence: 99%
“…The element numbers of the three models were 8,678 (Mesh 1), 15,998 (Mesh 2), and 23,998 (Mesh 3). If increasing the mesh number led to a change of ≤5% in the maximum displacement, the mesh was considered adequately refined [16,17]. The results demonstrated that the difference between Mesh 1 and Mesh 2 was 6.48%; In each model, the sagittal plane is shown on the left and the frontal plane on the right.…”
Section: Mesh Convergence Testmentioning
confidence: 99%